1969
DOI: 10.1021/jf60164a003
|View full text |Cite
|
Sign up to set email alerts
|

Formation of complexes between protein and tannic acid

Abstract: Tannic acid and protein interact to form soluble and insoluble complexes, and the latter are favored by a pH near the isoelectric point of the protein and an excess of tannic acid. As the concentrations decrease, higher ratios of tannin to protein are possible in soluble complexes. The number of sites on a gelatin molecule occupied per tannin molecule decreases as the tannin concentration increases. and this is accompanied by a decrease in the apparent equilibrium constant of binding between the tannic acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
270
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(282 citation statements)
references
References 6 publications
9
270
1
2
Order By: Relevance
“…This study showed synergism on the combined concentrations of the plant extracts under study at a lower concentration, with FICI ≤ 0.5, which was in consonance with an earlier report (though not FIC determined) by the same author (Ojo et al 2013a) (see Figure 1). Cowan (1999) Britto et al 2013;Tamil et al 2010;Van-Burden & Robinson 1981;Young & Greaves 1940;Zabri et al 2008) as in this study. By implication, the combination of these medicinal plants produces a greater efficacy in the treatment of staphylococcal wound infection as regularly experienced in orthodox medicines.…”
Section: Discussionsupporting
confidence: 57%
“…This study showed synergism on the combined concentrations of the plant extracts under study at a lower concentration, with FICI ≤ 0.5, which was in consonance with an earlier report (though not FIC determined) by the same author (Ojo et al 2013a) (see Figure 1). Cowan (1999) Britto et al 2013;Tamil et al 2010;Van-Burden & Robinson 1981;Young & Greaves 1940;Zabri et al 2008) as in this study. By implication, the combination of these medicinal plants produces a greater efficacy in the treatment of staphylococcal wound infection as regularly experienced in orthodox medicines.…”
Section: Discussionsupporting
confidence: 57%
“…Alkaloids were determined using, Harbone (1973) method, tannins (Van Buren andRobinson, 1969). Vitamins and minerals were determined by atomic absorption spectrophotometer (Pye Uniam SP8-190, Spec.…”
Section: Int J Plant Pathol 6 (2): 36-47 2015mentioning
confidence: 99%
“…The quantitative determination of tannin in Rue sample was performed as per protocol [15]. Briefly, 500 mg of the dried extract was dissolved in 50 ml of distilled water in a screw caped conical flask and allowed to shake for 1 h. Approximately 5 ml of filtrate was mixed with 2 ml of 0.1 M FeCl3 in 0.1 N HCl and 0.008 M potassium ferrocyanide.…”
Section: Quantitative Estimation Of Tanninsmentioning
confidence: 99%